2018
DOI: 10.1111/ap.12335
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Validity of Diagnostic Psychiatric Measures for Indigenous Australians

Abstract: Objective: There is limited research available regarding the prevalence rates of psychiatric illness in Indigenous Australians, and the available literature varies widely in terms of methods and findings. Culturally valid and appropriate tools are needed to ensure accurate outcomes. The purpose of this review is to examine the methods used to diagnose psychiatric disorders in Indigenous Australians and identify whether these are culturally appropriate or valid. Method: A systematic search of available literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…No studies were identified in this review that directly assessed a diagnostic or screening tool for eating disorders among Indigenous Australians. One systematic review aimed to examine the cultural validity of the methods used to diagnose psychiatric disorders among Indigenous Australians, however, it not include any articles directly assessing eating disorders, thus it was not included in this review [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were identified in this review that directly assessed a diagnostic or screening tool for eating disorders among Indigenous Australians. One systematic review aimed to examine the cultural validity of the methods used to diagnose psychiatric disorders among Indigenous Australians, however, it not include any articles directly assessing eating disorders, thus it was not included in this review [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This tool was designed and validated with multiple Indigenous communities across Australia and is free to use [ 21 ]. However, a systematic review of diagnostic methods for psychiatric disorders in Indigenous Australians did not identify any culturally specific or validated diagnostic or screening tools for eating disorders among Indigenous Australians [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We completed structured training for site staff, achieved high rates of interview completion, recruited an adequate number of participants with a MINI major depressive episode diagnosis to enable subgroup analyses, and complied with the National Health and Medical Research Council guidelines for Indigenous health research . Ideally, our criterion standard would have been a semi‐structured, culturally valid psychiatric interview, but such a diagnostic assessment is not available . However, the interviews were conducted by local, culturally aware clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of diagnostic psychiatric instruments found that none had been formally validated for Indigenous Australians . To rectify the paucity of Indigenous Australian‐specific depression research, a culturally adapted depression screening tool validated in multiple Australian states and territories is needed.…”
mentioning
confidence: 99%
“…Originally developed and validated with a sample of postnatal women in Scotland, the use of EPDS has gained widespread acceptance and extensive use over the ensuing 30 years evidenced by its ubiquitous translation and validation (Alvarado et al 2015;Cox et al 2014;Department of Health, Government of Western Australia 2006;Hewitt et al 2010;Joshi et al 2020;Rhee et al 2018;Shrestha et al 2016). However, in recent years, there has been emerging discussion around the limitations of the EPDS, including questioning of the cultural suitability and validity when applied in Indigenous or cross-cultural contexts (Black et al 2018;Gausia et al 2013;Geia et al 2013;State of Queensland 2014). A recent systematic review reported a lack of research investigating the effectiveness of the standard EPDS with Indigenous Australian women, providing neither psychometric properties nor qualitative validation of the standard EPDS (Kotz et al 2020).…”
Section: Introductionmentioning
confidence: 99%